2007
DOI: 10.1111/j.1468-0408.2007.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

In Between Curing and Counting: Performative Effects of Experiments With Healthcare Information Infrastructure

Abstract: Performance standards and accountability pervade modern healthcare. According to Michael Power, this may signify a new rationality of governance characterized by control of controls, which affects practices not by direct intervention, but through the processes by which practices are made auditable. The paper addresses this thesis by exploring the construction of a Danish standard for electronic patient records. It is shown that making healthcare auditable activates deep tensions between programs of clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Adolfsson and Wikström (2007) applied the concept of translation (Callon, 1986; and Latour, 1986) and neo‐institutional theory to their study of quality management in the Swedish municipality of Gothenburg while Skærbæk and Thorbjørnsen (2007) used an ANT framework to explore issues of identity and commodification in the Danish defence forces. In her study of the Danish Healthcare information infrastructure Vikkelsø (2007) drew on a variety of different theoretical perspectives including ANT, institutional theory and neo‐institutional theory, however, she states that the research is conducted on the basis of the ‘methodology of actor‐network theory’.…”
Section: Analysis Of Theories In Public Sector Accounting Researchmentioning
confidence: 99%
“…Adolfsson and Wikström (2007) applied the concept of translation (Callon, 1986; and Latour, 1986) and neo‐institutional theory to their study of quality management in the Swedish municipality of Gothenburg while Skærbæk and Thorbjørnsen (2007) used an ANT framework to explore issues of identity and commodification in the Danish defence forces. In her study of the Danish Healthcare information infrastructure Vikkelsø (2007) drew on a variety of different theoretical perspectives including ANT, institutional theory and neo‐institutional theory, however, she states that the research is conducted on the basis of the ‘methodology of actor‐network theory’.…”
Section: Analysis Of Theories In Public Sector Accounting Researchmentioning
confidence: 99%
“…These circulating ideas also influence existing tools and practices, and gradually change these existing devices. Several studies have reported on the implementation of new accounting devices and how this has given rise to resistance and change of both practice and practitioner (Kurunmäki, ; Skærbæk and Thorbjørnsen, ; Vikkelsø, ; and Rocher, ). In this study the focus has been on an existing medical professional tool and how this tool, invented for one purpose, gradually turned into a modern management device and found its governmental role for another.…”
Section: Resultsmentioning
confidence: 99%
“…In the accounting literature, ANT and the notion of translation has been used to emphasize how accounting devices emerge and transform (e.g., Preston, ; Lowe, ; Vikkelsø, ; and Rocher, ) and how performance auditing shapes identities (Skærbæk and Thorbjørnsen, ; and Justesen and Skærbæk, ). However, the issue of power and the construction of macro‐actors has been less developed (Czarniawska and Hernés, ).…”
Section: National Quality Registers As a Networkmentioning
confidence: 99%
“…A great deal of accounting (or more broadly speaking, management control) studies refer to (the concept of) construction (see Rutherford, 2000; Skærbæk, 2005; Vikkelsø, 2007; and Østergren, 2006). Nevertheless, most of the studies appear to apply the construction concept without explicitly defining it.…”
Section: Frame Of Referencementioning
confidence: 99%